Jenis Tindak Tutur Ilokusi pada Dialog Tokoh Utama dalam Novel Layangan Putus Karya Mommy ASF - Anisa, Ade Rifka; Wahyono, Hari; Dewi, Liana Sinta; Shalima, Irsyadi (UPA Bahasa Universitas Tidar And HISKI Kedu, 2023)
This research is motivated by the phenomenon of illocutionary speech acts in the dialog of the main character in the novel. The purpose of the research is to describe the types of illocutionary speech acts in the dialog of the main character in the novel Layangan Putus by Mommy ASF. The type of research used is descriptive qualitative. As for providing data, it uses the method of listening with the basic technique of tapping and then noting. In analyzing the data using the commensurate method with the technique of sorting the determining elements (PUP). The results of the research found are the types of illocutionary speech acts in the form of: (1) assertive includes explaining, proposing, expressing opinions, complaining, suggesting, stating, and boasting; (2) directive includes giving messages, giving permission, inviting, giving advice, and ordering; (3) commissive includes promising, offering, and threatening; and (4) expressive includes apologizing, praising, and thanking.